2022
DOI: 10.11158/saa.27.10.14
|View full text |Cite
|
Sign up to set email alerts
|

A new, broadly distributed species of predacious mites, Neoseiulus neoagrestis sp. nov., (Acari: Phytoseiidae) discovered through GenBank data mining and extensive morphological analyses

Abstract: A new species of phytoseiid mites, Neoseiulus neoagrestis sp. nov., was described based on all ontogenetic stages and extensive comparison with types/vouchers of closely related species and a thorough analysis of GenBank data. Mite specimens were collected in an area at the eastern coast of the Black Sea of Russia and cultured. Molecular barcoding revealed a close match (100–99.25%) with several unidentified COX1 sequences from Canada. Both Canadian and Russian mites reproduced sexually and had consistent morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Neoseiulus neoagrestis is a recently described phytoseiid species and nothing is known concerning its biological parameters on its prey (Khaustov et al 2022). However, our preliminary observations showed that it might be a promising candidate for the biological control of spider mites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoseiulus neoagrestis is a recently described phytoseiid species and nothing is known concerning its biological parameters on its prey (Khaustov et al 2022). However, our preliminary observations showed that it might be a promising candidate for the biological control of spider mites.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient amount of wheat bran was provided as a food source for the mites. The predatory mite, Neoseiulus neoagrestis was collected from moss in Sochi, Russia (Khaustov et al 2022). The stock culture of the predator was maintained in the plastic containers described above using T. putrescentiae as a food source.…”
Section: Mite Coloniesmentioning
confidence: 99%
“…Indeed, the importance of a single pair of solenostomes (gd8) to separate closely related species in the genus Kampimodromus, has previously been confirmed by molecular analyses in several cases (Tixier et al 2008;Döker et al 2018). A recent study also confirmed the taxonomic utility of gd2 in the systematics of Neoseiulus (Khaustov et al 2022). Interestingly, the authors reported a remarkable genetic distance (about 20%) and a different reproduction strategy (asexual vs sexual) between two morphologically identical species, except for the absence or presence of gd2, in the genus Neoseiulus.…”
Section: Introductionmentioning
confidence: 76%
“…In contrast, a series of identification keys are used the number of dorsal solenostomes for species delimitation in certain phytoseiid genera including Neoseiulus (Ragusa di Chiara & Tsolakis 1994;Kolodochka 2006;Papadoulis et al 2009;Kreiter et al 2010;Ferragut & Ueckermann 2012). Indeed, the importance of the presence or absence of a single pair of solenostomes to distinguish two otherwise identical species in some phytoseiid genera, such as Kampimodromus and Neoseiulus has previously been confirmed by molecular studies (Tixier et al 2008;Döker et al 2018;Khaustov et al 2022). Therefore, dorsal solenostomes seem to have great importance in taxonomy of Phytoseiidae and should be included in all future descriptions.…”
Section: Remarksmentioning
confidence: 99%
“…All morphological characters mentioned above are of great importance due to them being widely used in delimiting species within the Phytoseiidae family. For instance, several studies have demonstrated the taxonomic utility of a single pair of solenostomes when distinguishing between two morphologically identical species (Kolodochka 2018;Khaustov et al, 2022). Thus, to avoid taxonomic confusions, such characters should be correctly illustrated and described.…”
Section: Systematicsmentioning
confidence: 99%